2016
DOI: 10.1186/s12955-016-0412-z
|View full text |Cite
|
Sign up to set email alerts
|

Incremental validity of sense of coherence, neuroticism, extraversion, and general self-efficacy: longitudinal prediction of substance use frequency and mental health

Abstract: BackgroundSeveral studies have demonstrated the importance of sense of coherence (SOC), neuroticism (N), extraversion (E), and general self-efficacy (GSE) for health, yet the unique utility of these overlapping constructs remains uncertain. The present research aims at exploring incremental validity when predicting (1) substance use specifically and (2) mental health generally among adolescents.MethodsA prospective and longitudinal design was used to predict (1) initial substance use nine years into the future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 89 publications
3
43
1
4
Order By: Relevance
“…Considerable overlap between SOC and Neuroticism has been reported before (Feldt, Metsäpelto, Kinnunen, & Pulkkinen, 2007;Hochwälder, 2012). However, as our own data show, SOC contains unique variance that incrementally explains substance use over and above Neuroticism and other competing personality variables (Grevenstein, Bluemke, & Kroeninger-Jungaberle, 2014). Hence SOC cannot simply be equated with a positively framed (or reversed) version of Neuroticism.…”
Section: Discussionmentioning
confidence: 68%
“…Considerable overlap between SOC and Neuroticism has been reported before (Feldt, Metsäpelto, Kinnunen, & Pulkkinen, 2007;Hochwälder, 2012). However, as our own data show, SOC contains unique variance that incrementally explains substance use over and above Neuroticism and other competing personality variables (Grevenstein, Bluemke, & Kroeninger-Jungaberle, 2014). Hence SOC cannot simply be equated with a positively framed (or reversed) version of Neuroticism.…”
Section: Discussionmentioning
confidence: 68%
“…Based on SEM analyses, Sense of Coherence has shown better incremental predictive validity in relation to substance abuse and mental health above well-established measures of personality (i.e. neuroticism, extraversion, and self-efficacy) [ 62 ]. Mediation models also confirmed that Emotional Intelligence is a stronger predictor of Life Satisfaction above positive and negative affect [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have pointed towards the importance of differentiating salutogenic factors in mental health predictions via the SEM approach to allow new constructs to delineate their use and potential among theoretical or classical constructs [ 62 ]. The SEM approach should provide suitable evidence for construct-level incremental validity conclusions taking into account the possible pitfalls of measurement [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…factorial structure, internal consistency, or convergent validity) is lacking, possibly due to the small sample size. Prompted by this fact, and given that the study of the psychometric properties of SOC continues to grow [12][13][14][15] as additional studies in specific populations would provide a better appreciation of its psychometric potential, especially regarding its association with parameters that have attracted less attention such as suicidal risk in both health and disease, the aim of the present study was to examine the psychometric properties of the Greek version of the SOC-29 scale in two different samples: a. Patients with long-term conditions (LTCs) attending specialty clinics or the emergency department (ED), and b.…”
Section: Introductionmentioning
confidence: 99%